Assessment of the prognostic value of CA125 for miscarriage risk in patients with threatened abortion: A systematic review and meta-analysis. - Yurong Cao; Weiwei Li; Linna Ma (PLoS ONE)
Background Threatened abortion is a common obstetric complication where early risk stratification is crucial for clinical management. CA125, a glycoprotein biomarker produced by endometrial and trophoblastic tissues, may serve as a valuable prognostic indicator as its elevated levels often reflect placental inflammation or detachment in this condition. To systematically assess its clinical value, we conducted a meta-analysis evaluating the prognostic accuracy of serum CA125 levels for miscarriage risk in patients with threatened abortion. Methods We systematically searched Web of Science, Medline via PubMed, ScienceDirect, EMBASE, Geenmedical, Cochrane Library, and Wiley databases from inception to May 30, 2024 for studies evaluating either CA125's prognostic value for miscarriage risk in threatened abortion, or serum markers' prognostic value for pregnancy outcomes. Two researchers independently screened literature and extracted data. Study quality and evidence certainty were assessed using QUAPAS and GRADE frameworks respectively. Meta-analyses were performed using Stata 17 and Review Manager 5.3. Results A total of 13 studies involving 1166 patients with threatened abortion were included in this meta-analysis. The pooled estimates demonstrated that CA125 exhibited the following prognostic performance for predicting miscarriage risk in patients with threatened abortion: sensitivity, 89% (95% CI: 83-93%); specificity, 91% (95% CI: 84-95%); positive likelihood ratio (PLR), 10.2 (95% CI: 5.4-19.3); negative likelihood ratio (NLR), 0.13 (95% CI: 0.08-0.19); diagnostic odds ratio (DOR), 82 (95% CI: 31-212); and area under the summary receiver operating characteristic curve (SROC AUC), 0.95 (95% CI: 0.92-0.96). Elevated serum CA125 levels were significantly associated with an increased risk of miscarriage. According to the GRADE assessment, the certainty of evidence was moderate for sensitivity but low for other parameters, primarily due to heterogeneity, risk of bias, and other confounding factors. Conclusion Current evidence with moderate certainty indicates that serum CA125 demonstrates high prognostic value for assessing miscarriage risk in threatened abortion, particularly for identifying high-risk patients. However, due to low-certainty specificity findings, caution is warranted when using CA125 to rule out miscarriage. While these results support CA125's potential as a complementary tool to ultrasound, further studies are required to establish standardized cut-off values for clinical implementation.